Virtue and Delirium. The Boundaries of Imagination in Spinoza - de Pablos Escalante, Raúl (Escritura e Imagen, 2019)
In a letter from July 20 1664 (Ep. 17), Spinoza reply to his friend P. Balling, who previously told him of the experience of what can be considered as an acoustic hallucination. Balling recalled that he heard from his son, still healthy, similar moans as those he heard just before he died. It is possible to approach this letter from the study of the imagination and its relations with the affective reality; which confronts us with the dual aspect, psychical and physical, of affects. We will try to elucidate the complex network of notions present in this letter, taking into account the definitions of an image and of what is to imagine (Ethics 2P17s) and the distinction between trace and image (Vinciguerra, L., La semiotica di Spinoza, Pisa, Edizioni ETS, 2012.). The main questions that will served us as guide are: How can there be a trace of what has not happened? When the virtue of imagination can make us turn delirious?
Keywords: effects of the imagination; images; traces; affects; thought; understanding